Insulinotropic Effect of the Non-Steroidal Compound STX in Pancreatic β-Cells - Ropero, Ana B.; Alonso-Magdalena, Paloma; Soriano, Sergi; Juan-Picó, Pablo; Roepke, Troy A.; Kelly, Martin J.; Nadal, Ángel (PLOS ONE, 2012)
The non-steroidal compound STX modulates the hypothalamic control of core body temperature and energy homeostasis. The aim of this work was to study the potential effects of STX on pancreatic β-cell function. 1–10 nM STX produced an increase in glucose-induced insulin secretion in isolated islets from male mice, whereas it had no effect in islets from female mice. This insulinotropic effect of STX was abolished by the anti-estrogen ICI 182,780. STX increased intracellular calcium entry in both whole islets and isolated β-cells, and closed the KATP channel, suggesting a direct effect on β-cells. When intraperitoneal glucose tolerance test was performed, a single dose of 100 µg/kg body weight STX improved glucose sensitivity in males, yet it had a slight effect on females. In agreement with the effect on isolated islets, 100 µg/kg dose of STX enhanced the plasma insulin increase in response to a glucose load, while it did not in females. Long-term treatment (100 µg/kg, 6 days) of male mice with STX did not alter body weight, fasting glucose, glucose sensitivity or islet insulin content. Ovariectomized females were insensitive to STX (100 µg/kg), after either an acute administration or a 6-day treatment. This long-term treatment was also ineffective in a mouse model of mild diabetes. Therefore, STX appears to have a gender-specific effect on blood glucose homeostasis, which is only manifested after an acute administration. The insulinotropic effect of STX in pancreatic β-cells is mediated by the closure of the KATP channel and the increase in intracellular calcium concentration. The in vivo improvement in glucose tolerance appears to be mostly due to the enhancement of insulin secretion from β-cells.